Disclosure ESG: abordagens teóricas, métodos de avaliação e evidências empíricas - Damasceno, João Pedro Tavares (2025)
In a context marked by increasing demands for more responsible and transparent business practices, this dissertation, structured in the form of scientific articles, aims to investigate the phenomenon of ESG (Environmental, Social, and Governance) disclosure through different theoretical, methodological, and empirical approaches. It seeks to understand the factors that influence the disclosure of sustainable practices by organizations and to assess the authenticity of the information disclosed. The study begins with a bibliometric analysis of the international scientific literature on the topic, identifying trends, gaps, and predominant theoretical foundations. Based on Legitimacy Theory and Stakeholder Theory, a conceptual model is proposed that integrates governance and communication constructs as explanatory pillars of ESG disclosure. Subsequently, a methodology is developed to measure the level of disclosure, based on the comparison between sustainability reports and news published in the media, using a structured scoring logic. This methodology is applied to a sample of Brazilian state-owned and private companies operating across various economic sectors, revealing distinct patterns of engagement with ESG transparency, with greater consistency observed between discourse and practice among state-owned enterprises. Finally, the study investigates the factors that foster authentic organizational engagement with sustainability, highlighting the role of governance (Legitimacy Theory) and communication (Stakeholder Theory). The results contribute to the theoretical advancement regarding the motivations and forms of ESG disclosure, offer a practical tool for critically assessing organizational transparency, and strengthen the debate on the reliability of corporate sustainability practices. The dissertation concludes by emphasizing the importance of integrated approaches that combine theory, method, and empirical application in the field of corporate social and environmental responsibility.